Noncoding transcribed ultraconserved region (T‐UCR) UC.48+ is a novel regulator of high‐fat diet induced myocardial ischemia/reperfusion injury. Issue 6 (11th November 2018) - Ding, Lu; Gong, Chengxin; Zhao, Jiani; Liu, Xingzi; Li, Tao; Rao, Shenqiang; Wang, Shuo; Liu, Yuanyuan; Peng, Shanping; Xiao, Wen; Xiong, Chaopeng; Wang, Rumeng; et al.
Abstract: Increasing evidence has suggested high‐fat diet (HFD) is an independent risk factor for myocardial ischemia/reperfusion (MI/R) injury. Long noncoding RNAs (lncRNAs) recently attracted much attraction in the study of MI/R injury. However, the functional questions of specific lncRNAs in HFD‐induced MI/R injury have not been well elucidated. Uc.48+ is a lncRNA from a transcribed ultraconserved region (T‐UCR) of human, mouse, and rat genomes. Here, we explored the aggravating role of uc.48+and identified purinergic P2X7 receptor (P2X7R) as a downstream regulator of uc.48+ in HFD‐induced MI/R vulnerability. We demonstrated uc.48+ expression was upregulated, accompanied by the corresponding upregulation of P2X7R in HFD I/R myocardium and HFD‐induced MI/R vulnerability. Overexpression of uc.48+enhanced, whereas silencing of uc.48 + decreased the expression of P2X7R, cardiomyocyte apoptosis, and MI/R injury. The functional relevance of uc.48+ regulated P2X7R expression and the subsequent NF‐κB signaling to promote cardiomyocyte apoptosis was supported by inhibition of P2X7R with its specific antagonist (A438079) as well as the inhibitor of NF‐κB signaling (pyrrolidine dithiocarbamate, PDTC) in H9c2 hypoxia/reoxygenation (H/R) cells transfected with pcDNA3.0‐uc.48 + plasmid, and RNA immunoprecipitation (RIP) suggested uc.48+ could interact with transcription factor Sp1. Importantly, Sp1 inhibitor (mithramycin, MIT) was found to suppress uc.48+ ‐induced P2X7R expression and the NF‐κB signaling and cardiomyocyte apoptosis. Our findings provide a potential novel mechanism through which uc.48+ boosts cardiomyocyte apoptosis and MI/R vulnerability to HFD. Thus, uc.48+ is a novel regulator of HFD‐induced MI/R injury; targeting uc.48+ may be a novel therapeutic approach of MI/R vulnerability to HFD. Abstract : High‐fat diet (HFD) is an independent risk factor for myocardial ischemia/reperfusion (MI/R) injury. Uc.48+ is a long noncoding RNA (lncRNA) from a transcribed ultraconserved region (T‐UCR) of human, mouse, and rat genomes. Here, we explored the aggravating role of uc.48+ and identified purinergic P2X7 receptor (P2X7R) as a downstream regulator of uc.48+ in HFD‐induced MI/R vulnerability. Targeting uc.48+ may be a novel therapeutic approach of MI/R vulnerability to HFD.